REGULASI DIRI PADA IBU TUNGGAL YANG MEMILIKI ANAK REMAJA - Zawil Arham; Bahrun Bahrun; Abu Bakar (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2017)
Arham, Zawil 2016. Self Regulation In Single Mothers Who Have Children. Thesis, Department of Guidance and Counseling, the Faculty of Education, University of Syiah Kuala. Supervisor: (1) Dr.Bahrun, M. Pd, (2) Drs. Abu Bakr, M.Si Keywords: Self-Regulation, Single Mother, Teens This study entitled "Self Regulation In Single Mothers Who Have Children". The purpose of this study to find out how self-regulation in the single mother who has a teenage son. This research method is descriptive qualitative. The research location is housed in Johan Pahlawan sub-district of West Aceh district with 5 key respondents. The process of collecting data using interviews conducted during the first week. Data analysis using case analysis per respondent narrative. The results showed each of the respondents have a self-regulation vary. Each respondent memili its own way of regulating itself. Respondents first, second, fourth and fifth more democratic parenting apply to the child are free to express their opinions, while the third respondent is applying to authoritarian parenting. Single mothers in the district Gupta heroes have been able to regulate itself properly, they already have a clear objective and a plan to regulate the behavior of children.